DNA Replication in Time and Space: The Archaeal Dimension - Anastasia Serdyuk; Thorsten Allers (DNA)
The ability of a nucleic acid molecule to self-replicate is the driving force behind the evolution of cellular life and the transition from RNA to DNA as the genetic material. Thus, the physicochemical properties of genome replication, such as the requirement for a terminal hydroxyl group for de novo DNA synthesis, are conserved in all three domains of life: eukaryotes, bacteria, and archaea. Canonical DNA replication is initiated from specific chromosomal sequences termed origins. Early bacterial models of DNA replication proposed origins as regulatory points for spatiotemporal control, with replication factors acting on a single origin on the chromosome. In eukaryotes and archaea, however, replication initiation usually involves multiple origins, with complex spatiotemporal regulation in the former. An alternative replication initiation mechanism, recombination-dependent replication, is observed in every cellular domain (and viruses); DNA synthesis is initiated instead from the 3′ end of a recombination intermediate. In the domain archaea, species including Haloferax volcanii are not only capable of initiating DNA replication without origins but grow faster without them. This raises questions about the necessity and nature of origins. Why have archaea retained such an alternative DNA replication initiation mechanism? Might recombination-dependent replication be the ancestral mode of DNA synthesis that was used during evolution from the primordial RNA world? This review provides a historical overview of major advancements in the study of DNA replication, followed by a comparative analysis of replication initiation systems in the three domains of life. Our current knowledge of origin-dependent and recombination-dependent DNA replication in archaea is summarised.